Warfare and belligerence : perspectives in First World War studies - Purseigle, Pierre (Leiden ; Boston : Brill, 2005)
This collection of essays suggests some of the ways in which an interdisciplinary perspective may contribute to our understanding of the First World War. Its contributors examine the relationship between the character of the war and the nature of belligerent societies, and present original research on the comparative history of the Great War.
'It all goes wrong' / Dennis Showalter -- Discipline in the Italian Army 1915-1918 / Vanda Wilcox -- New Jerusalems / Patrick Porter -- Encountering the 'enemy' / Heather Jones -- Marc Sangnier's war, 1914-1919 / Gearóid Barry -- From liberalism to labour / Paul Mulvey -- Protest and disability / Jennifer D. Keene -- Huts, demobilisation and the quest for an associational life in rural communities in England after the war / Keith Grieves -- An American geographer between science and diplomacy / Nicolas Ginsburger -- The Great War and modern scholarship / Elizabeth Fordham -- New writers, new literary genres (1914-1918) / Nicolas Beaupré -- Women readers of Henri Barbusse / Leonard V. Smith -- Cinematic representations of the enemy in Belgian silent fiction films / Leen Engelen -- Paris, Berlin / Elise Julien.
Includes bibliographical references and index.
Print version record.
Electronic reproduction.
Master and use copy. Digital master created according to Benchmark for Faithful Digital Reproductions of Monographs and Serials, Version 1. Digital Library Federation, December 2002.
digitized
English.
Keywords: World War, 1914-1918 -- Social aspects; World War, 1914-1918 -- Historiography; War and civilization -- History -- 20th century; War and society -- History -- 20th century; Guerre mondiale, 1914-1918 -- Aspect social; Guerre mondiale, 1914-1918 -- Historiographie; Guerre et civilisation -- Histoire -- 20e siècle.; Guerre et société -- Histoire -- 20e siècle.; HISTORY -- Military -- World War I; Historiography; Social aspects; War and civilization; War and society; Weltkrieg; Geschichtsschreibung; Sozialgeschichte; Oxford; Eerste Wereldoorlog; Sociale aspecten; Geschiedschrijving; 1900-1999; History